RELATIONSHIP BETWEEN THE EXECUTIVE AND THE CONGRESS IN MEXICO, 1997- 2006. THE APPROVAL OF THE PUBLIC FINANCES IN TWO GOVERNMENTS WITHOUT MAJORITIES (Andamios, Revista de Investigación Social, 2011)
This paper focuses on the political significance of the legislative approval of the federal budget in Mexico under minority government between 1997 and 2006 in comparison with the unified government period under the Partido Revolucionario Institucional control until 1997. The article shows how the Mexican Congress has become an effective connection in the new political system and that this is the main explanation of the legislative influence over the federal budget in the recent political change.
Keywords: Federal budget; Congress; political change; democracy